PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATAKAN KEMAMPUAN BERBICARA PADA ANAK USIA DINI 4-5 TAHUN KELAS A DI PAUD AL-AMIN SIMPANG EMPAT TAHUN PELAJARAN 2023/2024 - Bunga Siti Mukaramah; Novi Cahya Dewi; Rona Rona (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This research stemmed from the lack of speaking skills in early childhood, prompting teachers to use audio-visual media to improve them. This study aims to obtain clear information on: 1) To determine the planning for using audio-visual media to improve speaking skills in grade A early childhood students aged 4-5 years at Al-Amin Early Childhood Education (PAUD) Simpang Empat in the 2023/2024 academic year. 2) To determine the implementation of audio-visual media use to improve speaking skills in early childhood students aged 4-5 years at Al-Amin Early Childhood Education (PAUD) Simpang Empat in the 2023/2024 academic year. 3) To evaluate the use of audio-visual media to improve speaking skills in early childhood students aged 4-5 years at Al-Amin Early Childhood Education (PAUD) Simpang Empat in the 2023/2024 academic year. Learning outcomes improved after using audio-visual media. This can be seen through evaluations, where PAUD teachers conducted guidance sessions for early childhood students who had difficulty understanding the material presented.